2018
DOI: 10.1016/j.blre.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn from ineffective erythropoiesis in thalassemia?

Abstract: Erythropoiesis is a dynamic process regulated at multiple levels to balance proliferation, differentiation and survival of erythroid progenitors. Ineffective erythropoiesis is a key feature of various diseases, including β-thalassemia. The pathogenic mechanisms leading to ineffective erythropoiesis are complex and still not fully understood. Altered survival and decreased differentiation of erythroid progenitors are both critical processes contributing to reduced production of mature red blood cells. Recent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 232 publications
(257 reference statements)
6
76
0
1
Order By: Relevance
“…As shown in Figure 4F, Previous studies have shown that perturbation of autophagy is detrimental for erythroid maturation and has been documented in condition with disordered erythropoiesis such as β-thalassemic syndromes or chorea-acanthocytosis or during iron deficiency. 4,39 Consistent with this hypothesis, in Fyn −/− mouse erythroblasts we found accumulation of the autophagy cargo protein p62, a marker of autophagy inhibition. 4,39 Consistent with this hypothesis, in Fyn −/− mouse erythroblasts we found accumulation of the autophagy cargo protein p62, a marker of autophagy inhibition.…”
Section: Impaired Autophagy Related To Mtor Activation Characterizesupporting
confidence: 85%
See 4 more Smart Citations
“…As shown in Figure 4F, Previous studies have shown that perturbation of autophagy is detrimental for erythroid maturation and has been documented in condition with disordered erythropoiesis such as β-thalassemic syndromes or chorea-acanthocytosis or during iron deficiency. 4,39 Consistent with this hypothesis, in Fyn −/− mouse erythroblasts we found accumulation of the autophagy cargo protein p62, a marker of autophagy inhibition. 4,39 Consistent with this hypothesis, in Fyn −/− mouse erythroblasts we found accumulation of the autophagy cargo protein p62, a marker of autophagy inhibition.…”
Section: Impaired Autophagy Related To Mtor Activation Characterizesupporting
confidence: 85%
“…Erythroid differentiation is characterized by the production of reactive oxygen species (ROS) in response to erythropoietin (EPO) and by the large amount of iron imported into the cells for heme biosynthesis. [2][3][4][5] Previous studies have shown that the mice genetically lacking Lyn (Lyn −/− ) display reduced STAT5 activation and defective response to phenylhydrazine-(PHZ) induced stress erythropoiesis. EPO activates a signaling cascade, involving Jak2, as the primary kinase, and Lyn, a Tyr-kinase of the Src family (SFK), as secondary kinase.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations